MODERASI PROFITABILITAS DAN LEVERAGE TERHADAP PENGARUH KEBIJAKAN DIVIDEN PADA NILAI PERUSAHAAN - Adi, Ida Bagus Sugita; Putra Astika, Ida Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Shareholders generally want a relatively stable dividend distribution because it reduces uncertainty about the expected returns from the investments they make. It can also increase shareholder confidence in the company so that the share value can also increase. This study aims to obtain empirical evidence of the effect of dividend policy on firm value and the ability of profitability and leverage variables as moderating variables. The approach used in this research is a quantitative approach in the form of causality. The location of this research was carried out on the Indonesia Stock Exchange in manufacturing companies listed during 2017-2019. The sampling method used in this study was a saturated sample and obtained 15 manufacturing companies that distributed dividends in a row during 2017-2019. The data were then analyzed using a moderated regression analysis test. The results of the study explain that the dividend policy variable has no effect on firm value, the leverage variable as a moderating variable strengthens the effect of dividend policy on firm value and the profitability variable is not able to moderate the effect of dividend policy on firm value